The Utterance of “Abtila’ ” and Calamity and Disorder as its Meanings in Al Baqrah Sura: An Objective Study (Islamic Sciences Journal, 2023)
The word affliction, sedition, calamity, ordeal, and test are words that share one meaning, which is “test and exam”, but some of them have meanings that are not included in the other, and the idiomatic meanings do not differ from the linguistic meanings.The study has shown that the people of affliction are of two types, the first category: the prophets, then the ideals, then the ideals, and the second category is of two types, the first type is those who were among the people of dereliction in worship, and the second type was those who were among the people of disbelief and debauchery.The wisdom of trial was to raise ranks, to distinguish between those who are steadfast in the truth and those who hesitate in it, to scrutinize the believers, to purify their ranks, and to settle souls on patience.By studying Surat Al-Baqarah as a model, it was found that there are different types of affliction, such as affliction with good and evil, affliction with magic (the temptation of magic), and affliction with assignment.The research concluded that calamities and tribulations afflict every human being without exception. Some of the calamities are at the level of the individual, such as illness, weakness, lack of money, and the death of the family. Other calamities are at the level of society and the world, such as wars, killing, displacement, sudden death, and the spread of epidemics and diseases, such as the Corona epidemic that shook the entire world and cancer. And many other diseases, all of which are a test and a test from Allah, Blessed and Exalted be He, to see what a person does, whether he is patient and supplicates to God, or is he dismayed.
Keywords: Word, affliction, calamity, sedition, Surat Al-Baqara